1981
DOI: 10.1161/01.res.48.3.352
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation properties of mammalian atrial muscle.

Abstract: SUMMARYThe properties of relaxation, in particular the sensitivity of relaxation to load, were analyzed in isolated intact atrial muscle and in manually dissected, detergent-treated cellular preparations from cat, dog, and rat atria. Force and length traces under increasing afterloads and following load clamps were obtained using an electromagnetic lever-force transducer system for the intact muscles and a capacitance transducer system for the cellular preparations. In both types of preparations, the time cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…In atrial myocytes, they are not expressed or lacked, which may reduce the mechanical synchronization of adjacent cells [38]. As a result, the relative contractile ability, i.e., force per cell cross-section, is lower in atrial muscles, as shown in previous studies [28,32,37] and in the present study.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…In atrial myocytes, they are not expressed or lacked, which may reduce the mechanical synchronization of adjacent cells [38]. As a result, the relative contractile ability, i.e., force per cell cross-section, is lower in atrial muscles, as shown in previous studies [28,32,37] and in the present study.…”
Section: Resultssupporting
confidence: 69%
“…In the human atrial myocardium, preload has been shown to affect both contractility and diastolic/systolic cytosolic Ca 2+ levels [32], while, in isolated atrial cardiomyocytes, no considerable effect of preload on Ca 2+ transient characteristics was observed [36]. Some other mammals showed weaker effects of preload compared to ventricular myocardium [37]. This may be explained by the prominent differences in the expression of ion channels, regulatory and contractile proteins of myofilaments, and by more subtle differences in the structure of the sarcoplasmic membrane between ventricular and atrial myocytes [4,7,9,10].…”
Section: Resultsmentioning
confidence: 99%
“…The following differences in the characteristics of the contractility and calcium kinetics between right atrial and right ventricular myocardium of rats can be highlighted: (i) the atrial myocardium develops lower active isometric tension (FSM is less effective); (ii) the mechanical tension develops and declines faster in the atrial myocardium; (iii) the maximal rate of cytosolic Ca 2+ elevation is lower and the time to peak of Ca transient is longer in the atrial myocardium; and (iv) the Ca transient decline does not show a "bump" phase, which is typical in the ventricular myocardium [21,24]. Compared to the ventricular myocardium, the length-dependent modulation of atrial myocardial contractility is much weaker in many mammals [13]. In addition, in rats with monocrotaline-induced right heart remodeling, SFR is increased in the right atrial myocardium (the present results) while it is decreased in the right ventricular myocardium, as we previously reported [20].…”
Section: Discussionmentioning
confidence: 99%
“…On atrial strips from human healthy donor hearts, it has been shown that length-dependent changes do exist and they relate not only to the mechanical characteristics of isometric twitch (FSM) but also to the kinetic characteristics of cytosolic calcium [12]. Compared to the ventricular myocardium, a weaker length-dependent modulation of atrial myocardial contractility has been shown in different mammals [13]. The contemporary changes in the mechanical activity and Ca transient in the atrial myocardium have been analyzed in a few studies [12,14], but these studies are limited to mechanically unloaded conditions or, at best, to different preloads.…”
Section: Introductionmentioning
confidence: 99%